Holocene relative shore level changes and Stone Age hunter‐gatherers in Hiiumaa Island, eastern Baltic Sea. (29th June 2020) - Rosentau, Alar; Nirgi, Triine; Muru, Merle; Bjursäter, Stefan; Hang, Tiit; Preusser, Frank; Risberg, Jan; Sohar, Kadri; Tõnisson, Hannes; Kriiska, Aivar
Abstract : Holocene relative shore level (RSL) changes and Stone Age palaeogeography of Hiiumaa Island are reconstructed using airborne LiDAR elevation data, sedimentological and archaeological proxies as well as GIS‐based landscape modelling. Altogether, 38 RSL index and limiting points are used in modelling and presented in the current paper. The highest raised shorelines of the Ancylus Lake and Litorina Sea, mapped at the elevations of 47 and 26 m a.s.l., formed around 10.3 and 7.4 cal. ka BP, respectively. The reconstructed RSL curve reveals a 20‐m drainage of Ancylus Lake followed by a land‐uplift‐driven 3‐m regression during the Initial Litorina Sea period. RSL rise during the Litorina Sea transgression remained below 4 m and its maximum was reached later than proposed previously, discarding therefore the idea of highly diachronous Litorina culmination in the eastern Baltic Sea. During the period 7.4–6.0 cal. ka BP, RSL fall was about 4.3 mm a −1, and afterwards in average at about 1 mm ‐1 less suggesting deceleration in isostatic rebound. suggesting deceleration in isostatic rebound. Palaeogeographical reconstructions show that during its earliest occupation at about 7.6 cal. ka BP less than 1% of the terrain of Hiiumaa was above the sea level and that wind‐protected SE exposed shores were the most preferred campsite locations of Late Mesolithic and Neolithic settlers. These campsites are located successively at lower elevations following the shoreline retreat and show repeated use of this coastal area between 7.6 and 4.6 cal. ka BP. Due to the spread of the Corded Ware culture around 4.8–4.0 cal. ka BP the settlements of Hiiumaa Island and many other coastal areas of the eastern Baltic moved from the coast to more suitable places for agriculture and animal husbandry.